Political pluralism and the state [ beyond sovereignty - Wissenburg, M. L. J [ (Marcel L. J.)] (Routledge innovations in politics theory, 2009)
Brings together IR, comparative politics and political theory approaches to analyze the post-sovereign state and develop a scheme for social and political scientists. This book seeks to understand and interpret political pluralization as an expression of the continuous processes of cooperation that define politics and legitimize institutions